Indonesian Halal Beauty Consumers’ Impulse Buying: Credibility, Awareness, and FoMO Explained - Saraswati, Nindya; Permana, Rezi Muhamad Taufik; Gumelar, Eka Tresna (MIMBAR : Jurnal Sosial dan Pembangunan, 2025)
Indonesia has a large and growing Muslim population, making it a significant market for halal beauty products. Consumers with high halal awareness are more discerning in their product choices, while credible influencers can effectively sway impulsive buying decisions. This empirical study aims to uncover how halal awareness and influencers credibility impact impulsive buying behaviour of halal beauty products and to explore how the fear of missing out (FoMO) moderates the relationships. This research is quantitative, which involves survey to 209 respondents and data analysis to quantify the relationships using SmartPLS4. The findings reveal significant positive correlation between halal awareness, influencer credibility and impulsive buying. Although FoMO shows a positive correlation with impulsive buying, its effect is not statistically significant. The moderating effect of FoMO role does not significantly show in the relationships. This research contributes to enrich liiterature, provide actionable insights for businesses and marketers in developing targeted marketing strategies that can encourage innovation and meet market demand.